Application of smoothed particle hydrodynamics to modeling mechanisms of biological tissue. (August 2016) - Palyanov, Andrey; Khayrulin, Sergey; Larson, Stephen D.
Highlights: We present a novel software package designed for the simulation of biological matter The first open source implementation of the PCISPH incompressible fluid dynamics algorithm Support for impermeable membranes, elastic matter and contractile matter Built on top of OpenCL for high performance and efficient multi-core CPU/GPU usage Cross platform support for Linux, Windows and Mac. Abstract: A prerequisite for simulating the biophysics of complex biological tissues and whole organisms are computational descriptions of biological matter that are flexible and can interface with materials of different viscosities, such as liquid. The landscape of software that is easily available to do such work is limited and lacks essential features necessary for combining elastic matter with simulations of liquids. Here we present an open source software package called Sibernetic, designed for the physical simulation of biomechanical matter (membranes, elastic matter, contractile matter) and environments (liquids, solids and elastic matter with variable physical properties). At its core, Sibernetic is built as an extension to Predictive–Corrective Incompressible Smoothed Particle Hydrodynamics (PCISPH). Sibernetic is built on top of OpenCL, making it possible to run simulations on CPUs or GPUs, and has 3D visualization support built on top of OpenGL. Several test examples of the software running and reproducing physical experiments, as well as performance benchmarks, are presented and future directions are discussed.